2018
DOI: 10.1177/2158244018809286
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nationality, Gender, and GPA on the Use of Reading Strategies Among EFL University Students

Abstract: and one of the main tools for independent language learning (Carrell & Grabe, 2002), reading has occupied a prominent place within language classrooms since the very onset of systematic language teaching and learning dating back to 4,000 years ago (Fotos, 2005). However, the conception of one's competence to read in the target language has been redefined over the course of time. Once perceived as mere decoders of images imprinted on a page (Carrell, Devine, & Eskey, 1988), readers have taken a more active role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…On the other hand, nationality proved to be a significant factor in cross-cultural sensitivity and intercultural effectiveness (Bećirović, Brdarević Čeljo, 2018;Bećirović et al, 2019). In these studies, Bosnian students achieved better results both in measuring metacognitive strategy awareness, on the one hand, and cultural sensitivity and intercultural effectiveness, on the other hand, than Turkish students (Bećirović et al, 2017, Bećirović, Brdarević Čeljo, 2018and Bećirović et al, 2019, but the difference is significant only when their cross-cultural sensitivity and intercultural effectiveness are measured. The conclusions that can be drawn from the aforementioned and are not in concordance with some previous findings (Rear, 2017;Roksa et al, 2017;etc.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…On the other hand, nationality proved to be a significant factor in cross-cultural sensitivity and intercultural effectiveness (Bećirović, Brdarević Čeljo, 2018;Bećirović et al, 2019). In these studies, Bosnian students achieved better results both in measuring metacognitive strategy awareness, on the one hand, and cultural sensitivity and intercultural effectiveness, on the other hand, than Turkish students (Bećirović et al, 2017, Bećirović, Brdarević Čeljo, 2018and Bećirović et al, 2019, but the difference is significant only when their cross-cultural sensitivity and intercultural effectiveness are measured. The conclusions that can be drawn from the aforementioned and are not in concordance with some previous findings (Rear, 2017;Roksa et al, 2017;etc.…”
Section: Discussionmentioning
confidence: 87%
“…When the results of the current study are compared to the results of other studies conducted in the Bosnian context among Bosnian and Turkish participants studying at international universities in Bosnia and Herzegovina, some interesting conclusions can be drawn. Namely, investigating metacognitive strategy awareness of Bosnian university-level students of different nationalities, namely Bosnian, Turkish and others, both Bećirović, Brdarević Čeljo and Dubravac (2018) and Bećirović, Brdarević Čeljo and Sinanović (2017) found that the impact of nationality on the use of metacognitive strategies was insignificant. On the other hand, nationality proved to be a significant factor in cross-cultural sensitivity and intercultural effectiveness (Bećirović, Brdarević Čeljo, 2018;Bećirović et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, following strategic steps while performing a reading task should be promoted in teaching practice whenever possible and at all educational stages, including a university level (Stahl, Armstrong, 2018) The current study is placed in the tertiary-education context of Bosnia and Herzegovina, the country where English seems to permeate all spheres of life (Delić et al, 2018;Dubravac, 2016;Dubravac et al, 2018;Dubravac, Skopljak, 2020;Kajtazović, 2012;Skopljak, Dubravac, 2020) and where English proficiency appears to be highly required (Kovačević et al, 2018). Despite such a strong and permanent presence of English in this context, either through formal instruction in the educational milieu or informal acquisition via the Internet, TV etc., Bosnian students still struggle to achieve the required competences, including reading competences (Dubravac, 2018;Kovačević et al, 2018). This might be at least partly changed by effective strategic behavior in various aspects of language use, including reading.…”
Section: Introductionmentioning
confidence: 99%
“…Students’ success, or more specifically, their learning performance, seems to be more related to their learning styles (Delić 2018 ; Mašić et al 2020 ), learning strategies they employ (Akay and Anvarovich 2015 ; Bećirović et al 2018 ; Delić and Bećirović 2018 ), their personal characteristics or their educational milieu (Bećirović and Brdarević-Čeljo 2018 ; Bećirović et al 2019 ; Fiossi-Kpadonou 2017 ; Kovačević et al 2018 ) and less to the mode of teaching. Bartholomew et al ( 2017 ), for example, found out that, in a middle-school sample study, students’ self-directed learning correlated more closely with the characteristics of students and classroom than with access to technology tools (p. 20).…”
Section: Discussionmentioning
confidence: 99%